Effectiveness of the Epley maneuver in patients with subjective vertigo at the ISSEMyM Toluca Medical Center - Seco-Fernández, Ana Carmen (2026)
Subjective benign paroxysmal positional vertigo (sBPPV) is a clinical variant of BPPV in which patients present with typical vestibular symptoms but without evidence of nystagmus during the Dix-Hallpike maneuver. Subjective benign paroxysmal positional vertigo accounts for approximately 20% of all BPPV cases and is frequently underdiagnosed in primary care settings. Our findings indicate that the Epley maneuver is equally effective in patients with subjective and objective BPPV, enabling timely intervention without the need for instrumental diagnostic methods. Objective: To evaluate the short-term effectiveness of the Epley maneuver in patients with sBPPV treated at Centro Médico ISSEMyM Toluca, as well as to analyze potential correlations with age, gender, and comorbidities. Methods: A quasi-experimental study was conducted in 49 patients diagnosed with sBPPV. The effectiveness of the Epley maneuver was assessed using the Dizziness Handicap Inventory (DHI) questionnaire at the initial consultation and at a 7-day follow-up. Results: 85.7% of patients achieved complete resolution of symptoms. The mean DHI score significantly decreased from 40.12 (±14.43) to 24.48 (±15.68) (p = 0.026). A negative correlation was observed between age and improvement in DHI scores (r = -0.32, p = 0.023). Discussion: The Epley maneuver proved to be highly effective. Its simplicity, accessibility, and zero cost make it a valuable tool in various clinical settings. The negative correlation between age and improvement highlights the need for closer follow-up in older patients to prevent falls. Conclusions: The Epley maneuver is an effective intervention for the management of sBPPV. While it is essential to rule out central pathology, once the diagnosis is established, addressing the patient's needs is crucial to optimize their quality of life and prevent complications.